2014
DOI: 10.1146/annurev-ecolsys-120213-091857
|View full text |Cite
|
Sign up to set email alerts
|

Mutualistic Interactions and Biological Invasions

Abstract: Mutualisms structure ecosystems and mediate their functioning. They also enhance invasions of many alien species. Invasions disrupt native mutualisms, often leading to population declines, reduced biodiversity, and altered ecosystem functioning. Focusing on three main types of mutualisms (pollination, seed dispersal, and plant-microbial symbioses) and drawing on examples from different ecosystems and from species-and community-level studies, we review the key mechanisms whereby such positive interactions media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
345
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 360 publications
(373 citation statements)
references
References 138 publications
4
345
2
5
Order By: Relevance
“…1; Theoharides and Dukes 2007;Richardson and Pyšek 2012). Consistently, most examples of novel mutualisms are both facultative and generalist (Traveset and Richardson 2014). This parallels our contemporary understanding of most native-native mutualisms (Blüthgen et al 2007).…”
Section: Novel Mutualisms As Examples Of Early Mutualism Formationmentioning
confidence: 55%
See 3 more Smart Citations
“…1; Theoharides and Dukes 2007;Richardson and Pyšek 2012). Consistently, most examples of novel mutualisms are both facultative and generalist (Traveset and Richardson 2014). This parallels our contemporary understanding of most native-native mutualisms (Blüthgen et al 2007).…”
Section: Novel Mutualisms As Examples Of Early Mutualism Formationmentioning
confidence: 55%
“…Ecologically and evolutionarily, mutualisms have shaped many biological invasions and vice versa (recently reviewed by Traveset and Richardson 2014). The importance of mutualisms in facilitating invasion and the potential for mutualism evolution to change as a result of biological invasions are critical areas of study (Kiers et al 2010;Traveset and Richardson 2014).…”
Section: Mutualisms As Important Structuring Forcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, different invaders can have positive effects on one another, leading to 'invasional meltdown' (Simberloff and von Holle 1999). For example, invasive woody plants may be dependent on co-invasion by invasion of their mutualists such as nitrogen fixing bacteria or ectomycorrhizal fungi (Nuñez and Dickie 2014;Traveset and Richardson 2014). Recent studies have also shown that invasive mammals can in turn facilitate the dispersal of invasive ectomycorrhizal fungal species required for the successful establishment of invasive tree species, in both Argentina (Nuñez et al 2013) and New Zealand (Wood et al 2015).…”
Section: Role Of Determinants Of Invasion: Context and Coinvasionmentioning
confidence: 99%